2021
DOI: 10.1007/s00401-021-02270-x
|View full text |Cite
|
Sign up to set email alerts
|

Wide distribution of prion infectivity in the peripheral tissues of vCJD and sCJD patients

Abstract: Sporadic Creutzfeldt-Jakob disease (sCJD) is the commonest human prion disease, occurring most likely as the consequence of spontaneous formation of abnormal prion protein in the central nervous system (CNS). Variant Creutzfeldt–Jakob disease (vCJD) is an acquired prion disease that was first identified in 1996. In marked contrast to vCJD, previous investigations in sCJD revealed either inconsistent levels or an absence of PrPSc in peripheral tissues. These findings contributed to the consensus that risks of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…The detection of PrP Sc in blood was also demonstrated in blood samples taken at the presymptomatic stage of vCJD [112]. No such detection of PrP Sc in blood has been described with other human prion diseases, although PMCA has recently detected PrP Sc in widespread peripheral tissues of sCJD patients [148].…”
Section: Peripheral Pathologymentioning
confidence: 97%
See 1 more Smart Citation
“…The detection of PrP Sc in blood was also demonstrated in blood samples taken at the presymptomatic stage of vCJD [112]. No such detection of PrP Sc in blood has been described with other human prion diseases, although PMCA has recently detected PrP Sc in widespread peripheral tissues of sCJD patients [148].…”
Section: Peripheral Pathologymentioning
confidence: 97%
“…More recently, the use of the in vitro conversion assay PMCA in the detection of minute quantities of PrP Sc has suggested that the distribution of PrP Sc in both clinical and asymptomatic vCJD cases, and sCJD cases may be more widespread than initially thought [147,148]. While PMCA is not currently included as a diagnostic tool for prion diseases, recent studies have demonstrated that PMCA protocols offer sufficient sensitivity and specificity for the amplification of minute amounts of PrP Sc in biological fluids from vCJD patients including, urine [149], blood [112,113,115] and CSF [150,151].…”
Section: Peripheral Pathologymentioning
confidence: 99%
“…Since the current PrP Sc disinfection/decontamination procedures had been developed using scrapie and CJD isolates before sCJD classification was established, the efficacy of these procedures against the V2 sCJD strain needs to be reconfirmed. In addition, as the presence of infectivity has been reported in a wide variety of peripheral tissues of sCJD MM1 patients including the lung, heart, kidney, pancreas, salivary gland, thyroid, adrenal gland, skeletal muscle, and lymphoid tissues [29], the distribution of infectivity in peripheral tissues should be investigated also in sCJD VV2 and MV2 patients. Furthermore, elucidation of the reason for the reduced infectivity of the M1 sCJD strain through the peripheral route will pave the way for the development of preventive measures against iatrogenic CJD transmission through peripheral routes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise relationship between prion strain diversity and the clinicopathological subtypes of sCJD remains imperfectly characterized, two strains named M1 CJD and V2 CJD seem to account for the most frequent forms of sCJD; M1 CJD is predominantly found in the brain of MM/MV1 sCJD patients, while the V2 CJD strain is generally found in VV/MV2 sCJD patients [ 8 , 9 , 11 , 14 ]. However, in up to 35% of sCJD patients the co-existence of both M1 CJD and V2 CJD strains was demonstrated by bioassay [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…These observations raised the hypothesis that different prion strains (most likely originating from undetected cases of sCJD in the donor population) contaminated the hGH preparations administered to recipients in the UK and in France, resulting in different incubation periods for each of the PRNP codon 129 subgroups between these countries [ 16 , 23 ]. This study aims to test this hypothesis by performing experimental transmissions of 22 hGH-iCJD brain homogenates from patients with all three codon 129 genotypes from France (11 cases) and the UK (11 cases) into a panel of well characterized human-PrP-expressing transgenic mice (tgHu), following an established methodology that has been used extensively to identify sCJD prion strains in a range of tissue samples from France, the UK and Spain [ 11 , 14 ]. Sporadic CJD cases originating from France and the UK were also used as controls in this study.…”
Section: Introductionmentioning
confidence: 99%